(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
This literature review shows the implementation of ICT, UVA, OVA and M - learning as digital resources in different learning environments in the subject of English, in order to demonstrate the strengthening of English language learning processes from various contents addressed with digital resources. Methodology: this study is framed in the bibliographic review of articles between research and publications in the Google Scholar search engine and in the Scielo and Redalyc databases. Results: 10 research articles published in the period 2018 to 2023 are analyzed, in which 70% are implementations that were carried out at different levels of schooling and therefore with specific topics with which the development of student learning is evaluated through the UVAs. Of the articles, 10% were in English and 90% in Spanish. Conclusions: it is evident that at present the UVA are indispensable in different learning environments from basic to higher levels, becoming tools that promote motivation, autonomy and strengthening the learning of a foreign language.